Fuel ethanol production: Process design trends and integration opportunities - Cardona, C.A.; Sánchez, O.J.
Current fuel ethanol research and development deals with process engineering trends for improving biotechnological production of ethanol. In this work, the key role that process design plays during the development of cost-effective technologies is recognized through the analysis of major trends in process synthesis, modeling, simulation and optimization related to ethanol production. Main directions in techno-economical evaluation of fuel ethanol processes are described as well as some prospecting configurations. The most promising alternatives for compensating ethanol production costs by the generation of valuable co-products are analyzed. Opportunities for integration of fuel ethanol production processes and their implications are underlined. Main ways of process intensification through reaction reaction, reaction-separation and separation-separation processes are analyzed in the case of bioethanol production. Some examples of energy integration during ethanol production are also ighlighted. Finally, some concluding considerations on current and future research tendencies in fuel ethanol production regarding process design and integration are presented.
Keywords: FUEL ETHANOL; PROCESS DESIGN; PROCESS SYNTHESIS; PROCESS INTEGRATION; CO-PRODUCTS